The Architecture of Indonesian Publication Index: A Major Indonesian Academic Database - Imam Much Ibnu Subroto; Tole Sutikno; Deris Stiawan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Journal articles are required all researchers as references to improve the quality of research so that the results are better than existing studies. The presence of many journal indexers that collect articles from many publishers and repositories are very helpful to lecturers and researchers to locate articles in their specific areas of interest. The main issues in the indexing include: (i) the selection and collection process articles data, (ii) the management of indexing based on source and relevance of science (iii) the accuracy and speed of the search process, and (iv) the relationship between the articles each other called citation. The desirable by readers from the indexer is to get relevant and good-quality articles easily and accurately. While the interest of the journal managers is to supply their article which reader preferred then hope many cited to their journals. This is where the position of an indexer to bridge publisher and reader. This paper presents the architecture of Indonesian Publications Index (IPI) as the bridge. This architecture is designed with three layers. The layers are the data collection layer, storage layer, and service layer. The functionality of the first layer is IPI collaboration with publishers, the second layer is the index management system, the third layer is a service to the readers. Service layer built on a variety of applications such as web based applications, mobile applications and e-library.